Validity of a booklet to promote the health of people with diabetes in the face of COVID-19 - Carla Lidiane Jácome dos Santos; Alex dos Santos Silva; Waleska de Brito Nunes; Jacira dos Santos Oliveira; Cizone Maria Carneiro Acioly; Thalys Maynnard Costa Ferreira; Marta Miriam Lopes Costa; Lidiane Lima de Andrade (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to validate the content and appearance of a booklet to promote the health of people with diabetes mellitus in the face of COVID-19. Methods: a methodological study, carried out in a virtual environment with experts who had practical and scientific experience in diabetes mellitus, from November 2021 to February 2022. Data were analyzed using the Content Validity Ratio. Results: twenty-seven experts from different states of Brazil and with different academic backgrounds participated in the study. In content validity, reviews were suggested in items in relation to objectives and structure, in appearance validity, adjustments in layout were suggested. Conclusions: the results showed that the booklet achieved adequate content and appearance validity rates. Therefore, when adapting to experts' suggestions, it becomes an accurate tool.